Risiko Produksi Karet Petani di Kecamatan Kejuruan Muda Kabupaten Aceh Tamiang - Fifi Ariska Siregar; Fiddini Alham; Thursina Mahyuddin; Muslimah (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2019)
The aim of this research to know the source of risk of rubber production, to analyze the affected of rubber production factors and price fluctuation affected of rubber production in Kejuruan Muda district, Aceh Tamiang region. The method used a survey. Analyze of rubber production of a source of risk used multiple linear regression with independent variable is a number of rubber tree died, a number of disease tree, climate and production month before and the dependent variable is production. The sources of rubber production risk are climate and pest. The number of died tree and tree with disease affected rubber production.